Film Remakes as Ritual and Disguise : From Carmen to Ripley - Zanger, Anat (Amsterdam University Press, 2006)
The first book-length account of the symbolic chains that link remakes and explain their disguises, Film Remakes as Rituals and Disguise is also the first book to explore how and why these stories are told. Anat Zanger focuses on contemporary retellings of three particular tales-Joan of Arc, Carmen, and Psycho-to reveal what she calls the remake's "rituals of disguise." Joan of Arc, Zanger demonstrates, later appears as the tough, androgynous Ripley in the blockbuster Alien III film and the God-ridden Bess in Lars Von Trier's Breaking the Waves. Ultimately, these remake chains offer evidence of the archetypes of our own age, cultural "fingerprints" that are reflective of society's own preferences and politics. Underneath the redundancy of the remake, Zanger shows, lies our collective social memory. Indeed, at its core the lowly remake represents a primal attempt to gain immortality, to triumph over death-playing at movie theatres seven days a week, 365 days a year. Addressing the wider theoretical implications of her argument with sections on contemporary film issues such as trauma, jouissance, and censorship, Zanger offers an insightful addition to current debates in film theory and cinema history.
Wat is de reden van filmproducenten voor het maken van een 'remake', waarin een succesvol verhaal opnieuw verteld wordt? En waarin schuilt de aantrekkingskracht voor het publiek om deze verhalen steeds opnieuw te beleven? Wat maakt Carmen, Jeanne d'Arc of Ripley zo bijzonder? Film Remakes as Ritual and Disguise is de eerste grondige studie die het fenomeen 'remakes' onderzoekt in de context van de filmgeschiedenis. Een zeer breed scala aan films, van Olympia tot Carmen Hip-Hopera, van Jeanne d'Arc tot Aliens en Breaking the Waves, en van Suzanne and the Elders tot de installatie van Hitchcocks Psycho in het Centre Pompidou in 2002 passeert daarbij de revue. Zanger laat zien op welke manier de 'remakes' een nieuwe betekenis krijgen door elkaar te versterken, net iets te veranderen of door naar elkaar te verwijzen. Dit nieuwe deel in de serie "http://www.aup.nl/filmculture">Film Culture in Transition is geschreven vanuit een multidisciplinair perspectief om zodoende de relatie te doorgronden tussen institutionele, intertekstuele en feministische benaderingen van film. Aan de hand van zeer uiteenlopende aspecten van de films toont Zanger hoe de lange schakel van 'remakes' gezien kan worden als een reeks vingerafdrukken die de heersende voorkeur en overtuiging van de filmindustrie blootlegt.
English
Keywords: Film, TV & radio; History; Society & culture: general; culture and history; motion pictures; vrouwenstudies; film; cultuur and geschiedenis; women and education, research, related topics